Interpersonal violence and depression in Brazil: A cross-sectional analysis of the 2019 National Health Survey. - Daniel Harding; Charlie F M Pitcairn; Daiane Borges Machado; Luis Fernando Silva Castro De Araujo; Christopher Millett; Thomas Hone (PLOS Global Public Health)
Depression and interpersonal violence are issues of increasing public health concern globally, especially in low-and-middle income countries. Despite the known relationship between interpersonal violence and an increased risk of depression, there is a need to further characterise the experience of depression in those who have experienced violence, to better develop screening and treatment interventions. A cross-sectional analysis was conducted on responses from the 2019 Brazilian National Health Survey. The prevalence of depression (both clinician-diagnosed, and Patient Health Questionnaire (PHQ-9) screened) were estimated by type of violence experienced in the preceding 12 months (none, physical violence, sexual violence, physical and sexual violence, or threat of violence). Logistic regression models assessed the associations between violence and depression after adjusting for socioeconomic and demographic factors. Of 88,531 respondents, 8.1% experienced any type of violence. Compared to those not experiencing violence, those who experienced any type of violence had a higher prevalence of clinician-diagnosed or PHQ-9-screened depression (e.g. the prevalence of clinician-diagnosed depression was 18.8% for those experiencing sexual violence compared to 9.5% for those not experiencing violence). Both undiagnosed and untreated depression were also more prevalent in those experiencing any type of violence. In logistic regression models, any experience of violence was associated with a higher odds of depression (e.g. aOR = 3.75 (95% CI: 3.06-4.59) for PHQ-9-detected depression). Experiencing violence was also associated with a higher likelihood of having depression which was undiagnosed (e.g. in those who experienced sexual violence: aOR of 3.20, 95% CI 1.81-5.67) or untreated (e.g. in those who experienced physical and sexual violence: aOR = 8.06, 95% CI 3.44-18.9). These findings highlight the need to consider screening for depression in those affected by violence, and to prioritise mental healthcare in communities affected by violence.